Ambiguous Perspective in Narrative Discourse: Effects of Viewpoint Markers and Verb Tense on Readers' Interpretation of Represented Perceptions. Issue 8 (17th November 2018) - van Krieken, Kobie
ABSTRACT: Narratives frequently represent perceptions that allow for multiple interpretations in terms of perspective: Perceptions can be interpreted from the narrator's viewpoint as well as the character's viewpoint. Two experiments examined the role of contextual viewpoint markers and verb tense in readers' interpretation of such ambiguous perceptions. Whereas verb tense did not affect perceptual attributions in Experiment 1, viewpoint markers did: Readers tended to ascribe an ambiguous perception more strongly to the character in stories with (vs. without) a viewpoint marker in the context. This finding was replicated and extended in Experiment 2, which examined the scope of perceptual attributions by measuring readers' interpretation of three subsequent ambiguous perceptions. Again, verb tense had no effect on perceptual attributions, whereas viewpoint markers did: Readers ascribed each of the three perceptions more strongly to the character in stories with (vs. without) a contextual viewpoint marker. These results advance our understanding of narrative perspective by revealing the influence of local linguistic viewpoint markers on readers' interpretation of stories stretches to the discourse level.